Semen quality of Bali bulls fed supplement of Mungbean sprouts and mineral mix - Hoesni, F.; Afzalani, A.; Fitriani; Nurhayati, N.; Raguati, R.; Firmansyah, F. (International Journal of Agricultural Technology, 2024)
The results showed that MBS and MBM supplementation significantly (P<0.05) increased semen volume, concentration, motility, viability, and integrity of membrane plasma and had no significant effect (P>0.05) on semen abnormality. MBS and MBM supplementation at P2 (basal diet + 1 kg MBS + 0.25 kg MBM) was more effective in improving the semen quality of Bali bulls